Current Problems of Training Pedagogical Staff for the Implementation of Inclusive Education - Kurbanova Muxabbat Mamadjanovna; Mustayeva Guldora Salaxiddinovna; Tulaboeva Gulorom Tulaboevna; Saydaliyeva Dilfuza Zairjanovna (Genius Journals, 2022)
Inclusion primarily involves the inclusion of all children in society, because children with disabilities most of all need a friendly educational environment, which at the same time would not be artificial. Programs specially developed for "special" children are implemented in the isolation of boarding schools. Correctional organizations create a closed world for the child, in which attention is focused on his “lack”. An inclusive approach gives children the opportunity to become part of society and live a real life.
Keywords: Human Dignity; Equal Rights; Inclusive Education; All-Round Development